Integrating Equality - Globalization, Women's Rights, Son Preference and Human Trafficking - Seo-Young Cho (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2011)
Employing economic and social globalization indicators, we empirically analyze whether globalization affects women's rights in the economic and social dimensions. Using panel data from 150 countries over the 1981-2008 period, we find that social globalization positively affects both women's economic and social rights, while the impact of economic globalization disappears when controlling for social globalization. Furthermore, we find that social globalization also reduces 'son preference' problems, prevailing in developing countries. However, (marginalized) foreign women, proxied with inflows of human trafficking, are not beneficiaries of such 'female-friendly' globalization effects.
Keywords: F15; J13; J16; O16; O19; 330; economic and social globalization; womens economic and social rights; son preference; human trafficking